Direct observation of the Mottness and p–d orbital hybridization in the epitaxial monolayer α-RuCl3. Issue 32 (2nd August 2022) - Wang, Zhongjie; Liu, Lu; Zheng, Haoran; Zhao, Meng; Yang, Ke; Wang, Chunzheng; Yang, Fang; Wu, Hua; Gao, Chunlei
Abstract : In this work, we grow and study the strained monolayer α-RuCl3 on graphene by MBE, STM and DFT calculations. The Mottness and the energy-resolved d–p hybridization, which underlie the mechanism of Kitaev physics, are clearly visualized and elaborated. Abstract : α-RuCl3, a promising material to accomplish the Kitaev honeycomb model, has attracted enormous interest recently. Mottness and p–d bonds play vital roles in generating Kitaev interactions and underpinning the potential exotic states of quantum magnets, and the van der Waals monolayer is considered to be a better platform to approach a two-dimensional Kitaev model than the bulk. Here, we worked out the growth art of an α-RuCl3 monolayer on a graphite substrate and studied its electronic structure, particularly the delicate orbital occupations, through scanning tunneling microscopy and spectroscopy. An in-plane lattice expansion of 2.67 ± 0.83% is observed and the pronounced t2g –pπ and eg –pσ hybridization are visualized. The Mott nature is unveiled by an ∼0.6 eV full gap at the Fermi level located inside the t2g –pπ manifold which is further verified by the density functional theory calculations. The monolayer phase of α-RuCl3 fulfills the a priori criteria of recent theoretical predictions of tuning the relevant properties in this material and provides a novel platform to explore the Kitaev physics.